Epidemiology of Bovine Pestiviruses Circulating in Italy - Luzzago, Camilla; Decaro, Nicola (Frontiers in Veterinary Science, 2021)
Pestiviruses are widespread and economically important pathogens of cattle and other animals. Pestivirus A (formerly known as Bovine viral diarrhea virus 1, BVDV-1), Pestivirus B (Bovine viral diarrhea virus 2, BVDV-2), and Pestivirus H (HoBi-like pestivirus, HoBiPeV) species are infecting primarily cattle. Like other RNA viruses, pestiviruses are characterized by a high degree of genetic variability. This high rate of variability is revealed by the existence of a number of viral subgenotypes within each species. In cattle, the highest number of pestivirus subgenotypes has been documented in European countries, particularly in Italy. The aim of this review is to report an up-to-date overview about the genetic diversity of pestiviruses in Italian cattle herds. All three bovine pestiviruses species have been identified in cattle population with variable frequency and geographical distribution. The genetic diversity of Italian pestiviral strains may have diagnostic and immunological implications, affecting the performance of diagnostic tools and the full cross-protection elicited by commercially available vaccines. Implementation and strengthening of coordinated approaches for bovine pestivirus control in Italy are recommended. Therefore, it would be extremely important to increase control and restriction measures to the trade of cattle and biological products of bovine origin, including those containing fetal bovine serum.